2020
DOI: 10.1158/2159-8290.cd-20-0215
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Mediated Internalization of Cytotoxic Agents inERBB2Amplified or Mutant Lung Cancers

Abstract: Amplification of and oncogenic mutations in ERBB2, the gene encoding the HER2 receptor tyrosine kinase, promote receptor hyperactivation and tumor growth. Here we demonstrate that HER2 ubiquitination and internalization, rather than its overexpression, are key mechanisms underlying endocytosis and consequent efficacy of the anti-HER2 antibody-drug conjugates (ADC) ado-trastuzumab emtansine (T-DM1) and trastuzumab deruxtecan (T-DXd) in lung cancer cell lines and patient-derived xenograft models. These data tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
141
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 44 publications
6
141
0
Order By: Relevance
“…Similarly, Li et al examined the three TKIs in combination with T-DM1. 35 Co-treatment with neratinib and T-DM1 in HER2 -amplified or HER2 -mutated cell lines enhanced HER2 ubiquitination and internalisation, thereby increasing T-DM1 activity. This seems to be specific to the irreversible inhibitor, as the addition of lapatinib or tucatinib to T-DM1 did not increase HER2 ubiquitination in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Li et al examined the three TKIs in combination with T-DM1. 35 Co-treatment with neratinib and T-DM1 in HER2 -amplified or HER2 -mutated cell lines enhanced HER2 ubiquitination and internalisation, thereby increasing T-DM1 activity. This seems to be specific to the irreversible inhibitor, as the addition of lapatinib or tucatinib to T-DM1 did not increase HER2 ubiquitination in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 44 recently reported that the HER2 antibody drug conjugate ado-trastuzumab emtansine (T-DM1) has significant clinical activity in HER2-mutant lung cancer, even in tumors with low HER2 expression. One hypothesis as to why HER2-mutant tumors with low HER2 expression are sensitive to T-DM1 is that mutation of HER2 may increase the efficiency of receptor internalization following antibody binding 45 . Consistent with this finding, the UCC14-PDX was highly sensitive to DS-8201a, a HER2 antibody drug conjugate, which was recently approved by the FDA for unresectable or metastatic HER2-positive breast cancer 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Responses were seen across all HER2 mutation subtypes. In a recent analysis of this study including an additional expansion cohort, the results of a total of 49 patients with HER2-amplified and/or -mutated tumors were reported [ 195 ]. The ORR was 50% in both cohorts.…”
Section: Her2 Alterationsmentioning
confidence: 99%